أخلاقيات الاستهلاك من منظور اسلامي وأثرها على قرار المستهلك دراسة عينة من المستهلكين بمدينة سطيف - بساس, حسين (جامعة الوادي - University of Eloued, 2022)
تناولت هذه الدراسة موضوع تأثير أخلاقيات الاستهلاك من منظور إسلامي على قرار المستهلك، كون اخلاقيات المستهلك تؤثر على سلوكه الاستهلاكي، حيث تتجلى أهمية هذه الاخلاقيات في الدور الذي يمكن أن تلعبه في ضبط عملية الاستهلاك كونها تعتبر عامل من العوامل التسويقية المؤثرة على سلوك المستهلك، وقد تم شرح هذه الاخلاقيات وإبراز اهم نقاطها ومرتكزاتها. تم الاعتماد على عينة من 382 مستهلكا بمدينة سطيف، حيت قمنا بتوزيع استبيان قصد تقيم درجة تأثير هذه الاخلاقيات والضوابط عليهم، وتوصلت الدراسة الى عدة نتائج أبرزها أن اخلاقيات الاستهلاك من منظور إسلامي لها أثر على قرار المستهلك. This study revolves around the topic of the impact of consumer ethics from an Islamic perspective on the consumer decision, as the importance of this ethics is reflected in the role that it can play in controlling the consumption process. Explaining these ethics and highlighting its most important points and foundations. A sample of 382 consumers in the city of Setif was relied upon. We distributed a questionnaire in order to assess the degree of impact of these ethics and controls on them. The study reached several results most notably that the ethics of consumption from an Islamic perspective have an impact on the consumer's decision.
Consumer ethics from an Islamic perspective and its impact on Consumer decision A study of a sample of consumers in Setif city
مقال
Keywords: الأخلاقيات الاسلامية ; قرار المستهلك ; الاقتصاد الإسلامي ; المستهلك المسلم; The Islamic ethics ; Consumer decision; Islamic economics ; The Muslim consumer